2008
DOI: 10.1080/00498250802468645
|View full text |Cite
|
Sign up to set email alerts
|

Human CYP3A4-introduced HepG2 cells:In vitroscreening system of new chemicals for the evaluation of CYP3A4-inhibiting activity

Abstract: 1. The aims were to attest whether HepG2-GS-3A4, a cell line into which the human CYP3A4 gene was introduced, can be used for a screening of chemicals that will inhibit CYP3A4 activity. 2. The capacity of the cells for metabolizing CYP3A4 substrates in vitro was evaluated. Also determined was the effect of CYP3A4 inhibitors and non-inhibitors on nifedipine hydroxylation. Western blot, immunohistochemostry and determination of beta-nicotinamide adenine dinucleotide phosphate (NADPH)-reductase activity were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…While CYP3A4 activity, like EROD activity, could be a suitable biomarkers of heavy metal exposure, studies on CYP3A4 activity have focused on the mechanisms of drug metabolism and their interactions in humans or rats [56][57][58][59][60][61][62][63][64], but not on the effects of environmental pollutants. In our study, the inverted U-shaped dose-response of CYP3A4 activity to Cd exposure seemed to be consistent with the hormetic hypothesis [65].The phenomenon of hormesis is probably related to the activation of adaptive pathways that are responsible for cellular and physiological homeostasis [66].…”
Section: Discussionmentioning
confidence: 99%
“…While CYP3A4 activity, like EROD activity, could be a suitable biomarkers of heavy metal exposure, studies on CYP3A4 activity have focused on the mechanisms of drug metabolism and their interactions in humans or rats [56][57][58][59][60][61][62][63][64], but not on the effects of environmental pollutants. In our study, the inverted U-shaped dose-response of CYP3A4 activity to Cd exposure seemed to be consistent with the hormetic hypothesis [65].The phenomenon of hormesis is probably related to the activation of adaptive pathways that are responsible for cellular and physiological homeostasis [66].…”
Section: Discussionmentioning
confidence: 99%
“…One‐hundred‐thousand cells were seeded onto 24‐well culture plates and grown to confluence. We previously reported that enzymatic reactions by CYP3A4, such as diazepam N‐desmethylation, diazepam 3‐hydroxylation, lidocaine monodeethylation, atorvastatin acid 2‐hydroxylation and nifedipine oxidation, were increased about 100 fold in HepG2‐GS‐3A4 cells compared with those in HepG2‐GS cells and that these metabolites were easily detected in the culture medium of the HepG2‐GS‐3A4 cells [10] . We also reported that the inhibitory effects of ketoconazole and cimetidine on CYP3A4 activity were adequately evaluated by nifedipine as a substrate of CYP3A4.…”
Section: Methodsmentioning
confidence: 99%
“…HepG2 cells, from a cell line that originated from human hepatoblastoma, were obtained from RIKEN Cell Bank (Tsukuba, Japan). HepG2‐GS‐3A4 cells, transduced with both hamster glutamine synthetase (GS) gene and human CYP3A4 gene, were established previously [8–10] . In short, pBudCE4 plasmid (Invitrogen, Carlsbad, CA, USA), which had two multi‐cloning sites with human cytomegalovirus gene and human elongation 1‐alpha subunit gene as promoters, was used for the vector after ligation with hamster Gs and human CYP3A4 genes; it was introduced by lipofection and positive clones were selected using the index of resistance against zeocin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations